Effectiveness of using incentives to improve parolee admission and attendance in community addiction treatment - Prendergast, Michael L. (Criminal justice and behavior, 2015)
This study is a randomized effectiveness trial of the use of incentives to improve treatment utilization among parolees in community treatment. In prison, Admission Phase parolees were randomized to either Admission Incentive (n = 31) or Education (n = 29). Attendance Phase parolees entering community treatment were randomized to Attendance Incentive (n = 104) or Education (n = 98). In the Attendance Phase, study participants received a monetary incentive for each day that they remained in treatment (up to 22 weeks). There was no main effect for incentives in either phase of the study (Admission to community treatment, Incentive 60% and Education 64%, p = .74; Intervention completion, Incentive 22% and Education 27%, p = .46). Using Cox regression, age, first arrest age, and type of parole status predicted time-in-treatment (p < .05), but treatment group did not. Providing incentives did not increase the likelihood that parolees enrolled in or stayed in community treatment. In light of other studies with similar outcomes, criminal justice practitioners who are considering the use of incentives should be aware that they may not produce the desired outcomes.